Evaluation of left ventricular function after sofosbuvir and daclatasvir regimen for chronic hepatitis C - Kareem Ali Maher; Reda Biomy Bastawesy; Mahmoud Mohammed Youssef; Wael Anwar Haseeb; Mariam Salah Zaghloul (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess left ventricular functions by echocardiography after 12 weeks of sofosbuvir-daclatasvir combination therapy. Method: The prospective cohort study was conducted from December 2019 to December 2021 at Kafrelsheikh University Hospital, Egypt, and comprised adult patients of either gender who had been referred to the Cardiovascular Department for cardiac evaluation and were found to be eligible for sofosbuvir-daclatasvir combination therapy. The patients were classified into five groups according to cardiovascular risk factors. Group 1 had no risk factors; Group 2 had many risk factors; Group 3 had only hypertension; Group 4 had diabetes only; and Group 5 had smoking as the only risk. All patients were assessed at baseline and at the end of the 12-week of antiviral combination therapy sofosbuvir 400 mg once daily dose and daclatasvir 60 mg once daily dose. Parameters checked were left ventricular ejection fraction, global longitudinal strain, wall motion abnormalities and diastolic function. Data was analysed using SPSS 23. Results: Of the 200 patients, 104(52%) were females and 96(48%) were males. The age range was 34-81 years, and 18(9%) patients were aged >70 years. There were 78(39%) patients in Group 1, 60(30%) in Group 2, 25(12.5%) in Group 3, Group 4 had 13(6.5%) and Group 5 had 24(12%) patients. There were no significant changes in mean ejection fraction, global longitudinal strain and wall motion abnormalities (p>0.05). Diastolic function had some significant parameters in each of the 5 groups (p<0.05). Conclusion: Sofosbuvir-daclatasvir combination therapy did not affect or impair left ventricular systolic or diastolic functions. Keywords: Stroke, Sofosbuvir, Antiviral, Hepatitis C, Chronic, daclatasvir, Coronary syndrome, Cardiovascular diseases, Echocardiography, Amiodarone, Recurrence, Smoking.